Chondrosarcoma: With Updates on Molecular Genetics. (15th February 2011) - Kim, Mi-Jung; Cho, Kyung-Ja; Ayala, Alberto G.; Ro, Jae Y.
Abstract : Chondrosarcoma (CHS) is a malignant cartilage-forming tumor and usually occurs within the medullary canal of long bones and pelvic bones. Based on the morphologic feature alone, a correct diangosis of CHS may be difficult, Therefore, correlation of radiological and clinicopathological features is mandatory in the diagnosis of CHS. The prognosis of CHS is closely related to histologic grading, however, histologic grading may be subjective with high inter-observer variability. In this paper, we present histologic grading system and clinicopathological and radiological findings of conventional CHS. Subtypes of CHSs, such as dedifferentiated, mesenchymal, and clear cell CHSs are also presented. In addition, we introduce updated cytogenetic and molecular genetic findings to expand our understanding of CHS biology. New markers of cell differentiation, proliferation, and cell signaling might offer important therapeutic and prognostic information in near future.